LGR5 expression and clinicopathological features of the invasive front in the fat infiltration area of pancreatic cancer - Masato Kamakura; Takeshi Uehara; Mai Iwaya; Shiho Asaka; Shota Kobayashi; Tomoyuki Nakajima; Yasuhiro Kinugawa; Tadanobu Nagaya; Takahiro Yoshizawa; Akira Shimizu; Hiroyoshi Ota; Takeji Umemura (BMC, 2022)
Abstract Background Leucine-rich repeat-containing G-protein-coupled receptor 5 (LGR5) is a strong cancer stem cell marker in colorectal cancer; however, there are many unclear aspects of LGR5 expression in pancreatic cancer. It has been reported that the interaction between tumor cells and stroma at the fat infiltration site has a significant effect on pancreatic cancer prognosis. Therefore, we report a clinicopathological study of LGR5 expression at the fat invasion front in pancreatic cancer. Methods LGR5 expression was analyzed in 40 pancreatic ductal adenocarcinoma cases with RNAscope, which is a newly developed high-sensitivity in situ hybridization method. Epithelial-mesenchymal transition (EMT) was analyzed by the expression of E-cadherin and vimentin via immunohistochemistry. Results LGR5-positive dots were identified in all cases, especially with glandular formation. In the fat invasion front, a high histological grade showed significantly reduced LGR5 expression compared with a low histological grade (p=0.0126). LGR5 expression was significantly higher in the non-EMT phenotype group than in EMT phenotype group (p=0.0003). Additionally, LGR5 expression was significantly lower in cases with high vascular invasion than in those with low vascular invasion (p=0.0244). Conclusions These findings suggest that decreased LGR5 expression in the fat invasion front is associated with more aggressive biological behavior in pancreatic ductal adenocarcinoma, with higher tumor grade, EMT phenotype, and higher vascular invasion.